PURIFICATION AND CHARACTERIZATION OF SOY COTYLEDON -GLUCOSIDASE - Santos, R. F.; Oliveira, C. F.; Varea, G. S.; Orradi Da Silva, M. L. C. [UNESP]; Ida, E. I.; Mandarino, J. M. G.; Carrao-Panizzi, M. C.; Ribeiro, M. L. L. (Wiley-Blackwell, 2013)
Glucosidase F42 of soy cotyledons was purified by ammonium sulfate fractionation, ion-exchange chromatography (CM-Sephadex-C-50, Sigma, St. Louis, MO) and gel filtration (Sephadex G-100, Sigma). The enzyme was purified 111.8-fold relative to its concentration in the crude extract. It had an apparent molecular mass of 53kDa in gel filtration experiments and produced a 33-kDa band in sodium dodecyl sulfate-polyacrylamide gel electrophoresis, suggesting that it is dimeric. The purified -glucosidase F42 was characterized as a glycoprotein after the identification of fucose, galactosamine and glucosamine by high-pressure anion-exchange chromatography-pulsed amperometric detector. Its highest activity was observed at pH5.0 and 45C, and it was stable for up to 4 days at 25C. The Km of the enzyme was 0.12mM p-nitrophenyl--d-glucopyranoside. -Glucosidase F42 showed specificity for different substrates, and its activity was inhibited by 1mM HgCl2, 10mM glucono--lactone or 150mM glucose and increased by 10mM MnCl2. PRACTICAL APPLICATIONS -Glucosidase is an enzyme that hydrolyzes -glucosidic bonds to liberate glucose and hydrolyzes isoflavones to release aglycones. Soy aglycones have been broadly investigated because of their biological activity in the prevention and treatment of some chronic diseases. Soy -glucosidase can be used in the food industry to alter soy isoflavones for the production of functional foods that are rich in aglycone isoflavones. Therefore, it was an established method of purification of the enzyme that has great biotechnological potential.